Design of An Ergonomic Portable Fire Hose Roller: A Simulation Study - Isamudin, Afiq; Mahmood, Salwa (Progress in Engineering Application and Technology, 2021)
Firefighters are often exposed to hazards and involved in physical activities which can cause various ergonomic related problems. In this case, manually rolling the fire hose while maintaining an awkward posture for a long period caused back pain. Therefore, an ergonomic portable fire hose roller was proposed to help firefighters at Pagoh Fire Station, Johor to overcome ergonomic problems when rolling the fire hose. SolidWorks was used to design the fire hose roller and using ANSYS to assess the strength of the chosen material which was aluminium alloy. The simulation from ANSYS showed a bending occurred at the roller part after applying force. In conclusion, material selection and the design of fire hose roller must be revised carefully. Further study can be carried out by more detailed design parameters and simulation process.